Executive Dysfunction in Frontotemporal Epilepsy Due to Traumatic Brain Injury - Dewa Putu Gde Purwa Samatra (Journal of Global Pharma Technology, 2019)
Traumatic brain injury has been recognized as a cause of epilepsy. Epilepsy could impair cognitive function and the cognitive profiles are as heterogenous as the epileptic syndromes themselves. In most idiopathic epilepsies, cognition is only mildly deteriorated or even normal, whereas symptomatic epilepsy disorders are accompanied by focal deficits according to the specific functions of the respective areas. Poor cognitive outcome is generally associated with an early onset and a long duration of the seizure and with poor seizure control. We report a 31-year-old man, with a specific generalized tonic clonic seizure during sleep since one year ago. MRI shows cystic encephalomalacia in left frontal lobe due to head trauma 3 years ago. This patient had executive function disorder which was caused by uncontrolled frontotemporal epilepsy due to traumatic brain injury. We propose AED and cognitive stimulation to be performed routinely to prevent further cognitive deterioration.Keywords: Executive function, Frontotemporal epilepsy, Traumatic brain injury.